Visualization of electric energy production in Posavje in a mixed reality environment - Jazbinšek, Jure (JET on-line, 2018)
New technologies for visualization enable new possibilities for data visualization. This paper deals with the challenge of presenting the production of electric energy in a specific geographic area for a specific period. Old-fashioned x-y graphs have been surpassed by using holographic mixed reality technology, with the Microsoft HoloLens device. The production of electric energy of multiple power plants was visualized with 3D columns that represent the volume of energy production. 3D columns representing each power plant are correctly scaled to match nominal energy output and dynamically present energy output. Each 3D column is correctly positioned on the heightmap of the Posavje region and gives volumetric visualization of local energy production in the region. Visualization is developed for mixed reality smart-glasses and enables the presentation of energy production anywhere.
Keywords: 3D visualization; 3D vizualizacija; electric energy production; električna energija; Microsoft HoloLens; proizvodnja električne energije